Improvement of singularity avoidance for three dimensional planar manipulators by increasing their degrees of freedom - Yahya, S.; Moghavvemi, M.; Mohamed, H.A.F. (2012)
This paper demonstrates the singularity avoidance of three dimensional planar redundant manipulators. It discusses how to make the planar manipulators more maneuverable by adding extra degrees of freedom to them. The manipulability and the parameter of singularity indexes have been calculated for three different degrees of freedom three dimensional planar redundant manipulators to show the effectiveness of the proposed method for singularity avoidance.